Cystic fibrosis related diabetes – causes, impact on health and management of patients. Issue 3 (November 2014) - Caraher, Marie‐Terese; Marshall, Sally
Abstract Cystic fibrosis is the commonest, life‐threatening recessively inherited disease in the Caucasian population. The disease process which primarily affects the lungs also damages both exocrine and endocrine pancreatic function. With increasing survival, cystic fibrosis‐related diabetes is becoming more prevalent increasing from 15% of adolescents with cystic fibrosis to 50% of adults. Impaired glucose tolerance is also common. Insulin secretion gradually decreases over time. Insulin resistance also occurs and can vary dramatically with intercurrent illness. Even mild degrees of hyperglycaemia adversely affect nutritional status and lung function. Good blood glucose control improves nutritional status and lung function. Cystic fibrosis‐related diabetes develops insidiously, so that annual screening is recommended, ideally by oral glucose tolerance testing. HbA1c is not sufficiently sensitive to identify early abnormalities in glucose tolerance. Aims of managing cystic fibrosis‐related diabetes are to relieve symptoms, maintain normal body weight and growth, improve lung function and improve life expectancy. Insulin is the treatment of choice and the regimen should be tailored to the individual. Initially, only rapid‐acting insulin with the main meal may be necessary, but as insulin secretion diminishes, a full basal‐bolus regimen becomes necessary. Individuals with cystic fibrosis struggle to consume sufficient calories, so that a high calorie, high fat diet is usually appropriate. Supplemental enteral nutrition, with matching insulin administration, is frequently required. Special situations, including pregnancy, require specific management. The psychological impact of cystic fibrosis‐related diabetes on the individual is enormous. Successful management requires support from a multi‐disciplinary team with the necessary specialist knowledge and skills.